Facing the Challenges of Globalization: Transforming Madrasah Education from Bilingual to International Classrooms - Supriyanto; La Hadisi; Pairin; Dirman; Raehang (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
This study examines the process of transforming bilingual classes into international classes at MTs Ummusshabri Kendari and analyzes the community's response to the transformation. This article used a case study approach; the research involved in-depth interviews, participatory observation, and document analysis. The results show that this transformation involved significant changes in curriculum, pedagogical approach, and learning infrastructure. MTs Ummusshabri adopted the Cambridge curriculum integrated with the national curriculum and Islamic values. The main challenges include improving teachers' competencies, providing adequate facilities, and balancing international standards and madrasah identity. Community response, especially parents, has been generally positive, although there are concerns regarding tuition fees and academic pressure. The transformation has improved students' English proficiency, critical thinking skills and global outlook. MTs Ummusshabri's success in integrating international standards with Islamic values makes it a potential model for other madrasahs in Indonesia. This research highlights the importance of curriculum adaptation that considers local needs and religious values in the context of international education.